2021
DOI: 10.1002/osp4.578
|View full text |Cite
|
Sign up to set email alerts
|

Family‐based interventions for preventing overweight or obesity among preschoolers from racial/ethnic minority groups: A scoping review

Abstract: Objective: This scoping review aimed to synthesize the published literature on family-based childhood obesity prevention interventions from 2015 to 2021 that focused on children 2-5 years of age from racial and/or ethnic minority households. Methods:A PICOS (population, intervention, comparison, outcome, and setting) framework was used to guide the development of the research question, search strategy, and inclusion/exclusion criteria. To be included, the study must have been a randomized controlled trial or q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 122 publications
0
13
0
Order By: Relevance
“…IM distinguishes 6 steps in the planning of health promotion programs, starting with defining a logic model of the problem (1) and a model of change (2), followed by the design (3), production (4) and implementation of the program (5), and, finally, the evaluation (6). Distinguishing various concrete indicators of cultural adaptation for each IM step allows an in-depth analysis of cultural adaptation.…”
Section: Cultural Adaptation From An Intervention Mapping Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…IM distinguishes 6 steps in the planning of health promotion programs, starting with defining a logic model of the problem (1) and a model of change (2), followed by the design (3), production (4) and implementation of the program (5), and, finally, the evaluation (6). Distinguishing various concrete indicators of cultural adaptation for each IM step allows an in-depth analysis of cultural adaptation.…”
Section: Cultural Adaptation From An Intervention Mapping Perspectivementioning
confidence: 99%
“…Various interventions have been developed and evaluated for the prevention of childhood obesity. Reviews have shown that a combined approach with a center-based component and a home-based component contributes significantly to the effectiveness of these interventions 4–6. This implies that the culture of families and parenting styles in the domestic situation are important contexts for preventive healthy lifestyle interventions for children in their early years.…”
mentioning
confidence: 99%
“…A 2021 review identified 14 family-based, obesity prevention interventions (2015-2021) in 2-5year-old tailored for children of racial and ethnic minoritized populations. Of the identified interventions, eight reported diet-related outcomes, all of which found improvements (13) .…”
Section: Introductionmentioning
confidence: 99%
“…A 2021 review identified fourteen familybased, obesity prevention interventions (2015-2021) tailored for 2-5-year-old children of racial and ethnic minoritised populations. Of the identified interventions, eight reported diet-related outcomes, all of which found improvements (15) . However, most studies that analysed diet did not assess overall diet quality, and instead focused on intake of specific food groups or energetic intake.…”
mentioning
confidence: 99%
“…Similarly, reported findings from childcare-based interventions targeting the social, cultural, and physical home environments have demonstrated promising impacts on children’s body mass index (BMI) and EBRBs [ 26 , 27 ]. However, a gap remains in culturally tailored intervention to target American Latino children and their families [ 28 , 29 ] who are at increased risk for obesity [ 30 ].…”
Section: Introductionmentioning
confidence: 99%